Migration patterns in Dublin county borough - Johnson, N (Economic & Social Studies, 1974)
In the last 15 years Dublin has undergone a dramatic change, from the fairly sleepy introverted capital of the 26 counties, it has been transformed into a relatively sophisticated and increasingly cosmopolitan financial and commercial centre. The large demand for office space has led to a change in function of an ever-growing number of buildings in the central city area, while the steadily increasing population is being housed and rehoused in new suburban estates around and beyond the city perimeter.
Keywords: Migration; Dublin